Ailanthus triphysa: a review of phytochemistry and pharmacology - Nguyen Duc Duy; Bui, Huu Tai; Nguyen, Thi Kim Thuy; Nguyen, Thi Hanh; Quach, Thi Thanh Van; Quan, Cam Thuy; Bui, Thi Phuong Thao; Phan, Van Kiem (Vietnam Journal of Science and Technology, 2025)
This article summarizes recent research reports on the chemical composition and biological activities of Ailanthus triphysa (Dennstedt) Alston. About 92 compounds have been found from this species, including 11 alkaloids, 48 ​​triterpenoids, 4 quassinoids, 5 steroids and diterpenoids, 2 flavonoids, 6 benzopyranoids, 10 fatty aldehydes, acids, and 6 other compounds. Many of the compounds have unique structures and exhibit potential biological activities including antibacterial, antioxidant, antifungal, anti-inflammatory, anticancer, and cytotoxic activities. This review aims to systematically provide research results on the botany, phytochemistry and pharmacology of Ailanthus triphysa